Penggunaan Aplikasi Phet Colorado terhadap Kemampuan Pemahaman Konsep Siswa pada Materi Pecahan Campuran (Universitas Palangka Raya, 2026)
This study aims to determine the abillity of students’ conceptual understanding of mixed fractions after the application of the PhET Colorado application in class VII of Muhammadiyah Pagar Alam Middle School in the 2025/2026 Academic Year. The subjects in this study were class VII.2 with 30 students with an average of 77. This study uses a pre-ekperimental design method one group pretest-posttest. Data collection techniques used in this study include tests and documentation data analysis techniques are stages carried out after all research data is collected. Through the PhET Colorado application, the percentage per indicator was obtained, the indicator restating the concept with an achievement of 63,50%, the indicator mathematical representation with an achievement of 74,78%, the indicator problem solving with an achievement of 95,00%, therefore the average reached 77,78%. So it can be in mixed fractions material on the ability of students’ conceptual understanding in class VII of Muhammadiyah Pagar Alam Middle School in the 2025/2026 Academic Year.